Paralelos entre duas escrituras: romântica e realista em Senhora, de José de Alencar - Silva, Gilson Lucas da (2017)
The presence of certain aesthetic-literary characteristics in Senhora (1875), written by José de Alencar, confirmed to it, among the other novels of the Brazilian writer, a greater degree of complexity and importance, already considered by brazilian literary criticism. This dissertation seeks to investigate, in this area, the emerging realism in Brazilian romanticism in decline at the end of the XIX century. It's intended to answer the following question: Are there any possible indicators of realism in the romantic Alencariana narrative? A confrontation between divergent critical positions was established, whose testimonies of the authors Antonio Candido, Roberto Schwarz, João Luiz Lafetá, Dante Moreira Leite and others have already pointed out some indicators of a realistic writing present in Senhora. A critical-analytical approach has been chosen from the stylistic strategies of Alencariana discourse (ambiguity, irony, dissimulation) through which a specific way of narrating/describing the fictional world originally structured by the Alencariana narrator is manifested. Also the point of view of the characters-people was prioritized, considering the design of the French theorist Michel Zéraffa. However, it has been revealed to us that critical fortune does not prestige certain stylistic details constituent of the romanesque in Senhora, absent aspects that revealed a different reading of the novel. From this angle, we can deduce that the realism manifested in Alencar's novel can't be evaluated in the same proportions with which it was configured by brazilian realist fiction critical of the XIX and XX centuries. It was verified the presence of two ambivalent consciences, whose enunciations, of Aurélia Camargo and Fernando Seixas, configure, respectively, the tension between two ambivalent realities, one subjective and one objective, in the expression and polysemy that announce the passage from romantic society to realistic in the Alencariana novel